Law | book | culture in the Middle Ages - Gobbitt, Thom (Explorations in Medieval Culture, 2021)
Law | Book | Culture in the Middle Ages takes a detailed view on the role of manuscripts and the written word in legal cultures, spanning the medieval period across western and central Europe.